US Conservative and Libertarian Experts and Solar Geoengineering: An Assessment - Jean-Daniel Collomb (European Journal of American Studies)
The goal of this article is to review the various positions taken by free-market conservative and libertarian public policy experts regarding solar geoengineering. A quantitative analysis and a qualitative analysis of the online publications of ten major free-market think tanks are provided with a view to determining whether free-market conservative and libertarian experts are embracing solar geoengineering as a key solution to climate change. Specifically, the article looks at how prominent solar geoengineering is in the publications of free-market think tanks, gauges their level of support for or hostility toward solar geoengineering, and lists the arguments that they use for or against it. The analysis shows that solar geoengineering is still a marginal topic of discussion in the world of free-market think tanks, but that a majority of the experts who have considered solar geoengineering tend to support funding for research, often as an alternative to mitigation policies.